Post-translational modifications confer amphotericin B resistance in Candida krusei isolated from a neutropenic patient - Zhang, Li; Xiao, Jinzhou; Du, Mingwei; Lei, Wenzhi; Yang, Weiwei; Xue, Xiaochun (Frontiers in Immunology, 2023)
Neutropenia is a common complication in the treatment of hematological diseases and the most common predisposing factor for invasion by fungi, such as Candida krusei. Recent studies have shown that C. krusei, a life-threatening pathogen, has developed resistance to amphotericin B (AMB). However, the mechanisms that led to the rapid emergence of this AMB-resistant phenotype are unclear. In this study, we found the sensitivity for AMB could be promoted by inhibiting histone acyltransferase activity and western blot analysis revealed differences in the succinylation levels of C. krusei isolated from immunocompromised patients and of the corresponding AMB-resistant mutant. By comparative succinyl-proteome analysis, we identified a total of 383 differentially expressed succinylated sites in with 344 sites in 134 proteins being upregulated in the AMB-resistant mutant, compared to 39 sites in 23 proteins in the wild-type strain. These differentially succinylated proteins were concentrated in the ribosome and cell wall. The critical pathways associated with these proteins included those involved in glycolysis, gluconeogenesis, the ribosome, and fructose and mannose metabolism. In particular, AMB resistance was found to be associated with enhanced ergosterol synthesis and aberrant amino acid and glucose metabolism. Analysis of whole-cell proteomes, confirmed by parallel reaction monitoring, showed that the key enzyme facilitating lysine acylation was significantly upregulated in the AMB-resistant strain. Our results suggest that lysine succinylation may play an indispensable role in the development of AMB resistance in C. krusei. Our study provides mechanistic insights into the development of drug resistance in fungi and can aid in efforts to stifle the emergence of AMB-resistant pathogenic fungi.